Erminio Corti, I manifesti delle avanguardie artistiche latinoamericane (1920-1935) (Altre Modernità, 2020)
Erminio Corti, I manifesti delle avanguardie artistiche latinoamericane (1920-1935)(Verona, Ombre Corte, 2018, 266 pp. ISBN 978-88-6948-111-6)di Alessandro Secomandi